Sistem Pemilihan Karyawan Terbaik Menggunakan Metode Simple Additive Weighting (SAW) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) Berbasis Web pada Kans Galeri - Achmad Lutfi Fuadi; Joko Suwarno; Yuliana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Employees is one of the most important components of which are owned by the company in its efforts to maintain the viability, evolving, the ability to compete and earn a profit. Kans Galeri only uses the system of direct management decisions in conducting employee performance appraisal and assessment results are also perceived to be a less precise problems on selection of the best employee in the company.In this study researchers will design the decision support system using the method of Simple Additive Weighting (SAW) and Technique For Order Performance By Similarity To Ideal Solution (TOPSIS) in optimal decision-making and assist in determining which method is better.